WEIGHT LOSS ASSOCIATED WITH SODIUM GLUCOSE COTRANSPORTER-2 INHIBITOR DURING RAMADAN: A SINGLE CENTRE EXPERIENCE - Guan, Goh Kian; Zakaria, Miza Hiryanti (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Muslims observed daytime fasting during Ramadan. During daylight, no food or water is allowed. Sodium glucose cotransporter-2(SGLT-2) inhibitor promotes renal caloric and water loss, and results in weight reduction. This study aimed to look at changes of weight and blood pressure among persons with diabetes newly started on SGLT-2 inhibitor. METHODOLOGY This was a prospective study done in April and May 2019 in Hospital Tengku Ampuan Afzan, Pahang, Malaysia. The study recruited Muslim subjects with established diabetes on treatment and are able to fast. They were given Empagliflozin® 25 mg daily 2 weeks run-in period and throughout Ramadan. Blood pressure is measured with Colin Press-Mate and weight measured with Gima body weight scale during recruitment and between 2nd to 4thweeks of Ramadan. Descriptive statistics and paired t-test were used for statistical analysis. RESULTS Thirty-four subjects were recruited, 2 refused to participate. Mean HbA1c was 10.08%. Mean weight before starting Ramadan was 78.36 kg and during Ramadan was 75.88 kg (mean delta weight -2.55 kg, 95% CI 1.74 – 3.21, p<0.001). Mean systolic BP reduced from 153.5 mmHg to 150.2 mmHg (p=0.615) and no changes for diastolic BP (82.7 vs 82.6 mmHg), p=0.971. CONCLUSION The positive effect of weight loss is observed in most subjects started with SGLT2 inhibitors prior to Ramadan. This effect is seen as early as 4 weeks. Though effect may be confounded by Ramadan fasting itself, average weight loss from EMPA-REG outcome trial was about 3 kg and peaked during first 12 weeks. SGLT2 inhibitors remains a choice of therapy for patients desiring weight reduction.